Intervention with fructooligosaccharides, Saccharomyces boulardii, and their combination in a colitis mouse model - Wu, Yan; Fu, Hao; Xu, Xu; Jin, Hui; Kao, Qing-jun; Teng, Wei-lin; Wang, Bing; Zhao, Gang; Pi, Xiong-e (Frontiers in Microbiology, 2024)
Objective To examine the effects of an intervention with fructooligosaccharides (FOS), Saccharomyces boulardii, and their combination in a mouse model of colitis and to explore the mechanisms underlying these effects. Methods The effects of FOS, S. boulardii, and their combination were evaluated in a DSS-induced mouse model of colitis. To this end, parameters such as body weight, the disease activity index (DAI), and colon length were examined in model mice. Subsequently, ELISA was employed to detect the serum levels of proinflammatory cytokines. Histopathological analysis was performed to estimate the progression of inflammation in the colon. Gas chromatography was used to determine the content of short-chain fatty acids (SCFAs) in the feces of model mice. Finally, 16S rRNA sequencing technology was used to analyze the gut microbiota composition. Results FOS was slight effective in treating colitis and colitis-induced intestinal dysbiosis in mice. Meanwhile, S. boulardii could significantly reduced the DAI, inhibited the production of IL-1β, and prevented colon shortening. Nevertheless, S. boulardii treatment alone failed to effectively regulate the gut microbiota. In contrast, the combined administration of FOS/S. boulardii resulted in better anti-inflammatory effects and enabled microbiota regulation. The FOS/S. boulardii combination (109 CFU/ml and 107 CFU/ml) significantly reduced the DAI, inhibited colitis, lowered IL-1β and TNF-α production, and significantly improved the levels of butyric acid and isobutyric acid. However, FOS/S. boulardii 109 CFU/ml exerted stronger anti-inflammatory effects, inhibited IL-6 production and attenuated colon shortening. Meanwhile, FOS/S. boulardii 107 CFU/ml improved microbial regulation and alleviated the colitis-induced decrease in microbial diversity. The combination of FOS and S. boulardii significantly increased the abundance of Parabacteroides and decreased the abundance of Escherichia–Shigella. Additionally, it promoted the production of acetic acid and propionic acid. Conclusion Compared with single administration, the combination can significantly increase the abundance of beneficial bacteria such as lactobacilli and Bifidobacteria and effectively regulate the gut microbiota composition. These results provide a scientific rationale for the prevention and treatment of colitis using a FOS/S. boulardii combination. They also offer a theoretical basis for the development of nutraceutical preparations containing FOS and S. boulardii.